PENGARUH IKLAN, ELECTRONIC WORD OF MOUTH DAN KEPERCAYAAN TERHADAP PURCHASE DECISION ONLINE SHOP - Eddy Santoso (2017)
This study was conducted to examine the influence of advertising, electronic word of mouth, and confidence in the purchase decision. The research data was taken from a single source, namely berrybenka.com website visitors. In this study the number of samples required is 87 respondents. This analysis method using Partial Least Square (PLS) is used to analyze the influence of variables. The results showed that among the three hypotheses, one of which was rejected because it was not significant. Details of the results begins as follows: (1) the ad does not significantly influence the purchase decision. (2) electronic word of mouth significant effect on purchase intention. (3) trust significantly influence the purchase decision. Based on the results, it is suggested that the company online shop berrybenka.com should pay attention to the variables used in this study. Subsequent studies, researchers expect to add other variables, including variables that were not analyzed in this study may eventually expand to the consumer purchase decision online shop berrybenka.com